Blockchain Pada Sistem Informasi Akuntansi: Potensi Dan Implikasinya Terhadap Kualitas Informasi Keuangan - Didik Heri Purnomo; Rina Tjandrakirana (GLOBAL SCIENTS PUBLISHER, 2026)
This research aims to explore the potential, key challenges, and implications of Blockchain technology implementation on the quality of financial information within Accounting Information Systems (AIS). Amidst increasing demands for data integrity and transparency, Blockchain emerges as a disruptive innovation offering distributed recording mechanisms. The method used is a Systematic Literature Review (SLR) of 35 scientific articles published between 2021–2026, sourced from Scopus and SINTA databases. The analysis is conducted using the Technology-Organization-Environment (TOE) framework and Agency Theory. Research findings indicate that Blockchain's technical features, such as immutability, decentralization, and smart contracts, have the potential to enhance the qualitative characteristics of financial information, particularly in aspects of reliability, timeliness, and verifiability through the concept of triple-entry accounting. However, massive implementation still faces significant hurdles, including the complexity of integration with legacy systems (ERP), high investment costs, lack of digital literacy among practitioners, and regulatory gaps. Furthermore, Blockchain radical transparency triggers managerial resistance as it limits discretion in earnings management. This study provides implications for organizations to prepare IT infrastructure and intellectual capital, and for regulators to accelerate the formulation of digital asset legal frameworks.